Caracterização citogenômica e Dna Barcoding de três espécies de Oecomys (Rodentia: Sigmodontinae) da Amazônia brasileira - Gomes Júnior, Renan Gabriel (Instituto Nacional de Pesquisa da Amazônia - INPA, 2014)
Among South American rodents, the Cricetiadae family contain the largest number of representatives allotted in a single subfamily, Sigmodontinae. Oryzomyini is one of the seven tribes recognized as Sigmodontinae, which is composed by 27 genera, including Oecomys genus with 16 species. This taxon presents a difficult systematic classification due to limited morphological variability and great karyotype differentiation. Therefore, this study aims to contribute to the chromosomal characterization and analysis of phylogenetic relationships among species of the Oecomys genus from Brazilian Amazon. In this study, 30 individuals were analyzed in four different regions. Four species were recognized as Oecomys auyantepui with two distinct cytotypes, 2n=64, FN=110 and 2n=66, FN=114, despite this, cytogenetic techniques employed were similar between the cytotypes. C banding revealed centromeric faint markings in all chromosomes, the 5S rDNA probe showed two marks, three marks were observed by silver-staining, and 4 for the 18S rDNA probe. The telomeric FISH showed an interstitial marking on both cytotypes of the sex chromosome X, indicating a possible chromosomal rearrangement. Molecular cytogenetic analysis supports the similarity, only one clade was formed with intraspecific distance of 1,41%, and high value of nodal support; For Oecomys bicolor no variation among cytogenetic techniques employed, with 2n=80 and FN=142 , constitutive heterochromatin was distributed by centromeres and spread by short arms of some chromosomes with conspicuous markings. Silver-staining showed 7 tags, which represent the active nucleolus organizer regions, and 24 markings with 18S rDNA probe, suggesting a possible duplication and dispersion of these sequences. The 5S rDNA probe showed 2 tags. Molecular analysis of 3 groups were performed with genetic distance between them ranging from 7, 12% to 13,44%, suggesting a species complex; Oecomys rutilus had 2n=54 and FN=90, distribution of heterochromatin was the faint type distribution with the centromeres , pericentromeric portion and terminal. Four markers were observed by silver-staining, as well as the 18S rDNA probe. The site ribosomal 5S showed only two markings. Two clades were formed by molecular analysis with high nodal support consistent with a geographical distribution among the specimens. Oecomys rex was considered basally among all Oecomys species in molecular analysis.
Keywords: Citogenética; Dna Barcoding; Oecomys (Rodentia: Sigmodontinae)